2016
DOI: 10.1371/journal.ppat.1005834
|View full text |Cite
|
Sign up to set email alerts
|

Latency Entry of Herpes Simplex Virus 1 Is Determined by the Interaction of Its Genome with the Nuclear Environment

Abstract: Herpes simplex virus 1 (HSV-1) establishes latency in trigeminal ganglia (TG) sensory neurons of infected individuals. The commitment of infected neurons toward the viral lytic or latent transcriptional program is likely to depend on both viral and cellular factors, and to differ among individual neurons. In this study, we used a mouse model of HSV-1 infection to investigate the relationship between viral genomes and the nuclear environment in terms of the establishment of latency. During acute infection, vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
85
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(89 citation statements)
references
References 96 publications
(109 reference statements)
2
85
2
Order By: Relevance
“…In addition, we noted delays in the degradation of SP100 mediated by ICP0, consistent with reduced colocalization of ICP0 with structures containing SP100 and Daxx (31). Because ND10 bodies appear to be predecessors of viral replication compartments in which viral DNA is made and packaged, the results suggest that ICP0 homes in on ND10 bodies to degrade PML and at the same time initiate the formation of replication compartments (33)(34)(35)(36)(37). In this report, we focus on SP100.…”
mentioning
confidence: 62%
“…In addition, we noted delays in the degradation of SP100 mediated by ICP0, consistent with reduced colocalization of ICP0 with structures containing SP100 and Daxx (31). Because ND10 bodies appear to be predecessors of viral replication compartments in which viral DNA is made and packaged, the results suggest that ICP0 homes in on ND10 bodies to degrade PML and at the same time initiate the formation of replication compartments (33)(34)(35)(36)(37). In this report, we focus on SP100.…”
mentioning
confidence: 62%
“…Multiple factors impact HSV latency and reactivation including the status of the chromatin structure of the latent viral genome (Bloom et al, 2010; Knipe and Cliffe, 2008; Lieberman, 2016), neuronal antiviral responses (Enquist and Leib, 2016; Maroui et al, 2016; Rosato and Leib, 2015), and microRNAs that suppress lytic gene expression (Flores et al, 2013; Pan et al, 2014). Once considered to be a suppressed static state, the concept of HSV latency has evolved to a more dynamic model (Bloom, 2016) to account for HSV-specific immune surveillance in latently infected ganglia (St Leger and Hendricks, 2011), viral subclinical shedding (Wald and Corey, 2007), and the detection of lytic gene expression in individual latent neurons (Russell and Tscharke, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Promyelocytic leukemia (PML) nuclear bodies (NBs) (also called ND10) are proteinaceous entities aimed to control viral infection as part of the cell and nucleus-associated intrinsic antiviral response but also through innate immunity associated with the interferon (IFN) response. Our recent studies have shown that PML-NBs tightly associate with incoming HSV-1 genomes in the nucleus of infected TG neurons in mouse models and in primary TG neuron cultures [15,16]. Hence, PML-NBs reorganize in structures called viral DNA-containing PML-NBs (vDCP-NBs), which are formed at early times during the process of HSV-1 latency establishment and persist during latency per se in a large subset of latently infected neurons in a mouse model of infection [15].…”
mentioning
confidence: 99%
“…Therefore, although at the entire TG level HSV-1 latency could be a dynamic process from a transcriptional perspective, at the single neuron level, a strict, transcriptionally silent, quiescence can be observed, and vDCP-NB-containing neurons are major contributors of this latent/quiescent HSV-1 state. In humans, vDCP-NB-like structures have also been observed in latently infected TG neurons [16], suggesting that vDCP-NBs are probably molecular hallmarks of the HSV-1 latency process, including in the natural host.…”
mentioning
confidence: 99%
See 1 more Smart Citation